The Potentials and Tourism Aspect of Gianyar Botanical Garden Based on Tri Hita Karana - Ni Komang Indra Mahayani; Bambang Soemardiono; Vincentius Totok Noerwasito (IPTEK Journal of Proceedings Series, 2020)
Tourism plays an important role in the development of a city. Gianyar Botanical Garden (KRG) is nature tourism that explores natural and cultural potential. The existing culture serves as a philosophy of life, values, and activities. Culture and architecture will produce traditional architecture. The problem that occurs in the botanical garden is the decrease in identity and visualization as tourism. This phenomenon causes the region does not have its characteristics. The Gianyar Botanical Garden (KRG) is a sector that needs to be redeveloped with the local culture. A relevant culture to redevelop the tourism sector using the Tri Hita Karana concept. Related to the culture, it aims to find out the potentials and aspects which have Tri Hita Karana cultural values consisting of Parhyangan, Pawongan, and Palemahan. This study used a naturalistic paradigm research method with a qualitative approach by collecting information through observations, interviews, and documentation. This study supported by walk-through analysis of patterns and activities. The result showed the natural potential and local culture influenced the development of tourism. Bali as a tourist destination must pay attention to Tri Hita Karana aspects as the basis in preserving, protecting, and exploring. The redevelopment of the Gianyar Botanical Garden (KRG) with cultural uniqueness so that tourism becomes harmonious about God, human beings, and the environment that can last for a long period.